Rancang Bangun Marketplace pada UMKM Terimbas Pandemi Covid-19 menggunakan Metodologi Pengembangan Waterfall dan Metode FIFO - Suparman, Kodim; Triayudi, Agung; Andrianingsih, Andrianingsih (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The Covid-19 pandemic that has occurred since 2020 entered Indonesia and has almost occurred in all parts of the world has resulted in the world being stopped due to the Covid-19 Pandemic, all its effects have been felt by all circles, one of which is business actors. Indonesia is one of the countries affected by the Covid-19 Pandemic, one of which is the Indonesian economy which is in the MSME business sector, especially the Micro sector, such as the perfume business, clothes distro, shoe shop, medium-scale traders. small down another. They are most affected by this Pandemic because since the implementation of the large social scale (PSBB) which has automatically reduced their sales turnover. Because consumers no longer come to them. Therefore, the authors created a website-based system to assist MSMEs in making sales. Which is where the buyer no longer has to come to the seller. The author hopes this website can help return to their sales turnover.